Sustainable thinking : ethical approaches to design and design management - Sherin, Aaris, ....- (London : Fairchild Books, 2013)
Sustainable Thinking explores how values and sustainability can reshape the way design management is practised and applied. The book discusses how designers can combine innovative creative thinking with analytical problem-solving skills to produce outputs that are business ready and ethically driven. Examples from a wide range of practitioners who work within the field of sustainable design are examined through case studies, and engaging activities suggest ways for students and practitioners to explore introducing sustainable thinking into their work.
Includes bibliographical references and index.
Keywords: Sustainable design